Benthic macroinvertebrate community shifts based on Bti-induced chironomid reduction also decrease Odonata emergence. (1st January 2023) - Gerstle, Verena; Manfrin, Alessandro; Kolbenschlag, Sara; Gerken, Maximilian; Islam, A.S.M. Mufachcher Ul; Entling, Martin H.; Bundschuh, Mirco; Brühl, Carsten A.
Abstract: Chironomid larvae (Diptera: Chironomidae) often dominate aquatic macroinvertebrate communities and are a key food source for many aquatic predators, such as dragonfly and damselfly larvae (Odonata). Changes in aquatic macroinvertebrate communities may propagate through terrestrial food webs via altered insect emergence. Bacillus thuringiensis israelensis (Bti)-based larvicides are widely used in mosquito control but can also reduce the abundance of non-biting chironomid larvae. We applied the maximum field rate of Bti used in mosquito control three times to six mesocosms in a replicated floodplain pond mesocosm (FPM) system in spring for two consecutive years, while the remaining six FPMs were untreated. Three weeks after the third Bti application in the first year, we recorded on average a 41% reduction of chironomid larvae in Bti-treated FPMs compared to untreated FPMs and a shift in benthic macroinvertebrate community composition driven by the reduced number of chironomid, Libellulidae and Coenagrionidae larvae (Odonata). Additionally, the number of emerging Libellulidae (estimated by sampling of exuviae in the second year) was reduced by 54% in Bti-treated FPMs. Since Odonata larvae are not directly susceptible to Bti, our results suggest indirect effects due to reduced prey availability (i.e., chironomid larvae) or increased intraguild predation. As Libellulidae include species of conservation concern, the necessity of Bti applications to their habitats, e.g. floodplains, should be carefully evaluated. Graphical abstract: Image 1 Highlights: Bti (2.88 × 10 9 ITU/ha) was applied three times per year over two years. In treated floodplain pond mesocosms (FPM), chironomid larvae were reduced by 41%. Community shift was explained by fewer chironomid, Libellulidae and Coenagrionidae. Emergence of Libellulidae was reduced by 53% in Bti-treated FPMs. Aquatic effects may propagate to terrestrial food webs via reduced insect emergence.